Efflux-Pump Derived Multiple Drug Resistance to Ethambutol Monotherapy in Mycobacterium tuberculosis and Ethambutol Pharmacokinetics-Pharmacodynamics - Srivastava, Shashikant (2010)
BACKGROUND: In the treatment of tuberculosis, ethambutol is used in case there is isoniazid resistance. We examined for the emergence of drug resistance to ethambutol monotherapy in pharmacokinetic-pharmacodynamic studies in the hollow fiber system. METHODS: Dose–effect studies and dose-scheduling studies were carried out with ethambutol and log-phase growth Mycobacterium tuberculosis to identify exposures and schedules linked to optimal kill and resistance suppression. In one study, after 7 days of ethambutol 300 mg/day isoniazid was administered to each system to determine its early bactericidal activity (EBA). RESULTS: Efflux-pump blockage reduced the mutation frequency to ethambutol 64-fold. In dose-effect studies, ethambutol had a maximal EBA of 0.22 log(10) CFU/ml/day, as encountered in patients. By day 7, resistance had arisen to both ethambutol and isoniazid. Prior exposure to ethambutol abolished isoniazid EBA. Daily therapy, as opposed to more intermittent therapy, was associated with the least proportion of efflux-pump driven resistance, consistent with time driven effect. Microbial kill was best explained by the ratio of area under the concentration-time curve to minimal inhibitory effect (r(2)=0.90). CONCLUSION: Induction of an efflux-pump that reduces effect to multiple drugs provides an alternative pathway to sequential acquisition of mutations in the development of multiple drug resistance.